2014
DOI: 10.1371/journal.pone.0088658
|View full text |Cite
|
Sign up to set email alerts
|

Starvation Induces Phenotypic Diversification and Convergent Evolution in Vibrio vulnificus

Abstract: Starvation is a common stress experienced by bacteria living in natural environments and the ability to adapt to and survive intense stress is of paramount importance for any bacterial population. A series of starvation experiments were conducted using V. vulnificus 93U204 in phosphate-buffered saline and seawater. The starved population entered the death phase during the first week and approximately 1% of cells survived. After that the population entered a long-term stationary phase, and could survive for yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…These mutations allow the mutants to effectively scavenge the nutrients released by dead cells ( Zambrano and Kolter, 1996 ). A number of Gram-positive bacteria such as Listeria monocytogenes ( Bruno and Freitag, 2011 ), Staphylococcus aureus, Enterococcus faecalis , and Bacillus globigii ( Finkel et al, 1997 ) and Gram-negative bacteria including Campylobacter, Geobacter, Vibrio, E. coli, Pseudomonas , etc., have been found to enter the GASP state ( Chen and Chen, 2014 ). Gefen et al (2014) coined the term ‘constant activity stationary phase’ (CASP) to describe the phenomenon of constant rate of protein synthesis observed in non-growing bacteria that have undergone over more than 60 h of starvation.…”
Section: Physiology Of the Stationary Phasementioning
confidence: 99%
“…These mutations allow the mutants to effectively scavenge the nutrients released by dead cells ( Zambrano and Kolter, 1996 ). A number of Gram-positive bacteria such as Listeria monocytogenes ( Bruno and Freitag, 2011 ), Staphylococcus aureus, Enterococcus faecalis , and Bacillus globigii ( Finkel et al, 1997 ) and Gram-negative bacteria including Campylobacter, Geobacter, Vibrio, E. coli, Pseudomonas , etc., have been found to enter the GASP state ( Chen and Chen, 2014 ). Gefen et al (2014) coined the term ‘constant activity stationary phase’ (CASP) to describe the phenomenon of constant rate of protein synthesis observed in non-growing bacteria that have undergone over more than 60 h of starvation.…”
Section: Physiology Of the Stationary Phasementioning
confidence: 99%
“…These studies often reported changes in cell morphology and composition and pointed to a link between these changes and transition to the VBNC phenotype [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Other proteins that became undetectable in starved cells were the methyl-accepting chemotaxis protein I and the flagellin FLIC_ECOLI. Chen and Chen [54] demonstrated that under starvation, Vibrio vulnificus populations exhibited reduced motility. Lemke et al [55] and Chandrangsu et al [56] concluded that DksA (protein required for the regulation of certain promoters) and the alarmone ppGpp inhibit expression of the flagellar cascade during cells' entry into the stationary phase or during their starvation.…”
Section: Resultsmentioning
confidence: 99%